Selective antagonism of amino acid-induced and synaptic excitation in the cat spinal cord. - Davies, J (1979)
1. The effects of D-alpha-aminoadipate (DalphaAA), D-alpha-aminosuberate (DalphaAS) and other excitatory amino acid antagonists have been compared on the excitatory responses of neurones of the cat spinal cord to acetylcholine, a range of glutamate-related amino acids and stimulation of appropriate excitatory synaptic pathways. The ionophoretic technique was used for administration of excitants and antagonists. 2. DalphaAA and DalphaAS had little or no effect on acetylcholine-induced excitation of Renshaw cells. Responses of either Renshaw cells or dorsal horn neurones in the spinal cord to excitatory amino acids were depressed in the order: N-methyl-D-aspartate (NMDA), L-homocysteate, D-glutamate, ibotenate greater than D-homocysteate, L-aspartate, D-aspartate greater than L-glutamate, kainate and quisqualate. 3. These effects are consistent with the existence of different excitatory amino acid receptors, one type being sensitive to the actions of the antagonists, and activated predominantly by the NMDA group of excitants, with other receptors being relatively insensitive to DalphaAA and DalphaAS and activated predominantly by quisqualate and kainate. On this hypothesis, many amino acids are assumed to have mixed actions on DalphaAA-sensitive and -insensitive receptors. 4. 2-Amino-4-phosphonobutyrate (2APB) and L-glutamic acid diethyl ester (GDEE) produced different patterns of antagonism of excitatory amino acid-induced responses from those observed with DalphaAA and DalphaAS. Neither substance was as potent as DalphaAA or DalphaAS as an excitatory amino acid antagonist. 5. Both DalphaAA and DalphaAS selectively antagonized synaptic excitation of Renshaw cells evoked by dorsal root stimulation without affecting cholinergic excitation of these cells evoked by ventral root stimulation. These latter responses were selectively antagonized by dihydro-beta-erythroidine (DHbetaE). DalphaAA also antagonized synaptic excitation of unidentified dorsal horn neurones of the spinal cord evoked by dorsal root stimulation. Neither GDEE (particularly) nor 2APB were as effective as DalphaAA or DalphaAS as depressants of synaptic excitation. 6. Taken in conjunction with the results of in vitro studies on the specificity of action of Dalpha¿ and related substances, these observations suggest that certain synaptic excitations in the spinal cord are mediated by an excitatory amino acid transmitter, and that this transmitter interacts with receptors which are activated selectively by NMDA, less selectively by other amino acids, including L-aspartate, and probably only slightly by quisqualate, kainate and (exogenous) L-glutamate.